Pengaruh Profitabilitas, likuiditas, dan Solvabilitas Terhadap kinerja keuangan PT Semen Indonesia (Persero) Tbk pada periode 2020–2024 - ., Murniati; ., Firsta; Martha, Amy la (Jurnal Akuntansi Keuangan Dan Perpajakan | E-ISSN : 3063-8208, 2026)
This study aims to analyze the effect of profitability, liquidity, and solvency on the financial performance of PT Semen Indonesia (Persero) Tbk during the period 2020–2024. This research employs a quantitative associative approach using secondary data in the form of the company’s annual financial statements. Profitability is measured by Return on Assets (ROA), liquidity by Current Ratio (CR), solvency by Debt to Asset Ratio (DAR), and financial performance by Return on Equity (ROE). The data analysis techniques include descriptive statistics, classical assumption tests, and multiple linear regression analysis. The results show that partially, profitability, liquidity, and solvency do not have a significant effect on financial performance. However, simultaneously, these three variables have a significant effect on the financial performance of PT Semen Indonesia (Persero) Tbk.